2000
DOI: 10.1002/1097-0339(200101)24:1<39::aid-dc1006>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Fine-needle aspiration cytologic diagnosis of giant-cell tumor of the sacrum presenting as a rectal mass: A case report

Abstract: A giant‐cell tumor of the sacrum is rare, and poses significant therapeutic and surgical difficulties largely because of its location. Patients usually present with pain in the lower back radiating to one or both lower limbs, with or without neurological deficit. The index case presented with difficulty in defecation, in addition to pain in both lower limbs for 6 mo. The patient was seen to have a rectal mass, and a per‐rectal fine‐needle‐aspiration was performed. The smears showed a cellular aspirate composed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Giant cell tumours account for 5.12% of primary bone tumours and 22.7% of the benign tumours. 3,4 Approximately 84% of these tumours occur in patients older than 19 years. 3 All of the patients in our series were between 15-25 yr, with three of the four being Ն20 yr.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Giant cell tumours account for 5.12% of primary bone tumours and 22.7% of the benign tumours. 3,4 Approximately 84% of these tumours occur in patients older than 19 years. 3 All of the patients in our series were between 15-25 yr, with three of the four being Ն20 yr.…”
Section: Discussionmentioning
confidence: 99%
“…Saikia et al 4 reported a GCT of the sacrum diagnosed on FNAC. However the FNA in their case was performed per rectally.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 GCT of the bone has been included within the diagnostic purview of cytopathologists in recent times. 6,7 GCT is considered to be potentially malignant as recurrences and distant metastases are known to occur in some cases. 4 Vetrani et al also demonstrated that FNA biopsy permits an accurate cytopathological diagnosis of GCT.…”
Section: Discussionmentioning
confidence: 99%
“…5 Some cases of GCT of bone presenting at unusual sites were diagnosed exclusively by FNAC. 6,7 GCT is considered to be potentially malignant as recurrences and distant metastases are known to occur in some cases. GCT of the iliac bone can be aspirated by ultrasound-guided FNA which is safe and free of complications.…”
Section: Discussionmentioning
confidence: 99%
“…11 Vague abdominal discomfort, early satiety, and a change in bowel/bladder habits are possible. Neurological symptoms, if present, are often subtle.…”
mentioning
confidence: 99%